Per- and polyfluoroalkyl substances and blood pressure in pre-diabetic adults—cross-sectional and longitudinal analyses of the diabetes prevention program outcomes study. (April 2020) - Lin, Pi-I D.; Cardenas, Andres; Hauser, Russ; Gold, Diane R.; Kleinman, Ken P.; Hivert, Marie-France; Calafat, Antonia M.; Webster, Thomas F.; Horton, Edward S.; Oken, Emily
Highlights: The relationship between PFAS and blood pressure is unclear. The study examined this relationship among prediabetic adults in US over 15 years. There were small associations between PFAS and BP at baseline. Baseline PFAS were not associated with longitudinal changes in BP over time. Baseline PFAS were not associated with incidence of hypertension over time. Abstract: The relationship of plasma concentration of per- and polyfluoroalkyl substances (PFAS) with blood pressure (BP) is uncertain. This study examined cross-sectional and prospective associations of PFAS with BP and hypertension. We quantified plasma PFAS concentrations from 957 participants enrolled in the lifestyle and placebo arms of the Diabetes Prevention Program (DPP), a randomized controlled trial with approximately 15 years of follow-up. We used multivariable linear and logistic regressions to test cross-sectional associations of six PFAS, including perfluorooctanesulfonic acid (PFOS), perfluorooctanoic acid (PFOA), perfluorohexane sulfonic acid (PFHxS), N-ethyl-perfluorooctane sulfonamido acetic acid (EtFOSAA), N-methyl-perfluorooctane sulfonamido acetic acid (MeFOSAA), and perfluorononanoic acid (PFNA), with BP and hypertension prevalence, respectively, at baseline. We used generalized linear mixed models to estimate longitudinal associations between baseline PFAS and the rate of BP changes, and Cox-Proportional hazard models to estimate risk of developing hypertension relative to baseline PFAS. Models were adjusted for baseline age, sex, race/ethnicity, treatment arm, educational attainment, income, marital status, smoking habit, alcohol drinking, and diet. We tested for effect modification by the treatment arm and sex, and accounted for multiple comparisons using the False-Discovery Rate (FDR). PFAS concentrations and hypertension prevalence within the study population (65.3% female, 57.7% White, 65.3% aged 40–59 years) were comparable to the general U.S. population. Cross-sectionally, we found small but statistically significant associations of baseline plasma concentrations of PFOA with systolic BP (β per doubling: 1.49 mmHg, 95% CI: 0.29, 2.70); and MeFOSAA with hypertension (RR = 1.09 per doubling, 95% CI: 1.01, 1.19). Estimates were not statistically significant after FDR adjustment. Longitudinally, we observed null associations in the placebo arm, but some inverse associations of baseline PFOS and MeFOSAA with systolic BP in the lifestyle arm, perhaps due to regression toward the mean. Baseline PFAS concentrations also were not prospectively associated with hypertension risk. Overall, there were modest and mostly null associations of plasma PFAS concentrations with BP and hypertension.